Employee Motivation and Healthcare Quality in the Post-COVID-19 Pandemic: A South African Public Health Sector Perspective (Journal of Management & Business, 2025)
Motivating employees is key to the effectiveness and quality of healthcare services, particularly in the public health sector of South Africa. Despite its significant contribution to national health achievements, this sector frequently encounters obstacles that impede the provision of high-quality health services. This article made use of a qualitative method and used secondary data to explore the key elements that affect employee motivation, examine its impact on healthcare service quality, and identify strategies to boost motivation. The findings show that healthcare providers who lack motivation often face burnout, diminished morale, and disengagement, leading to inefficiencies and inadequate patient care. To tackle these issues, the article recommended enhancing the work environment, offering increased remuneration, establishing opportunities for career advancement, improving leadership approaches, and promoting the well-being of employees. Putting these strategies into practice is vital for cultivating a motivated workforce capable of delivering high-quality healthcare and achieving the broader objectives of equitable and sustainable healthcare in South Africa.